Development and validation of nomogram models to discriminate between acute aortic syndromes and non-ST-elevation myocardial infarction during troponin-blind period - Tong, Fei; Wang, Yue; Sun, Zhijun (Frontiers in Cardiovascular Medicine, 2023)
Background: Blood test-based methods of distinguishing between acute aortic syndromes (AASs) and non-ST-elevation myocardial infarction (NSTEMI) during the troponin-blind period of less than 2-3 hours of symptom onset have not been studied previously. We aimed to explore whether routine biomarkers might facilitate differential diagnosis. Methods: Data were retrospectively collected from 178 patients with AASs and 460 patients with NSTEMI within 3h of onset. Differential risk factors related to AASs were identified by univariate and multivariate logistic regression analyses for patients with onset<2h and onset≥2h respectively in cardiac troponin (cTn) cohort. Nomograms were established in cTn cohort as training set and validated in high-sensitivity cTn cohort. To assess the utility of the models in clinical practice, decision curves analyses were performed. Results: D-dimer, fibrinogen, age were identified as differential risk factors for AASs with onset<2h. D-dimer at optimal cutoff level of 281ng/mL for AASs had a sensitivity of 86.4% and a specificity of 91.3%. The nomogram was developed and validated with areas under the curve (AUC) of 0.934 (95% CI: 0.880–0.988), 0.952 (95% CI: 0.874–1.000), respectively. D-dimer, neutrophil, bilirubin and platelet were the differential risk factors for AASs with onset≥2h. D-dimer at optimal cutoff level of 385ng/mL has a sensitivity of 91.8% and a specificity of 91.3%. AUC of the second nomogram in training set and validation set were 0.965 (95% CI: 0.942–0.988), 0.974 (95% CI: 0.944–1.000), respectively. Conclusion: Time-dependent quality of D-dimer should be considered for discriminating AASs from NSTEMI. Both nomogram models may have clinical utility for evaluating probability of AASs.